The Legal Validity of Information Technology Utilization by Judges in Supervising the Execution of Criminal Sentences - Rd. Dewi Asri Yustia; Faris Fachrizal Jodi (Yustisia, 2026)
The oversight and monitoring of the implementation of criminal sentences represent a vital yet inadequately developed aspect of Indonesia’s criminal justice system, especially in achieving sentencing goals such as rehabilitation, deterrence, and social reintegration. This article is urgent because criminal penalties are getting more complicated, judges have too much work to do, and information and communication technology (ICT) is moving too quickly for the Criminal Procedure Code (KUHAP) to keep up. The study aims to examine the legal obstacles encountered by courts in the oversight of criminal offenders via ICT and to develop a suitable legislative framework that confers binding legal authority to such technology. Utilizing a normative juridical methodology encompassing statutory, conceptual, philosophical, and comparative frameworks, this study examines Indonesian criminal procedural law in conjunction with comparative practices from several jurisdictions. The findings indicate substantial normative deficiencies in KUHAP regarding the utilization of ICT for judicial oversight and monitoring, leading to the constrained efficacy of post-sentencing supervision. The study suggests the explicit integration of ICT-based supervision standards into KUHAP to enhance judicial oversight of sentence implementation. The study enhances the evolution of criminal law by promoting discourse on criminal law policy, especially in reconciling procedural law reform with technological advancements and the changing aims of punishment.